2016
DOI: 10.1016/j.jnc.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

‘Ecosystem service opportunities’: A practice-oriented framework for identifying economic instruments to enhance biodiversity and human livelihoods

Abstract: Economic instruments that promise “win-win” solutions for both biodiversity conservation and human livelihoods have become increasingly popular over recent years. There however remains a gap in terms of practical and policy-relevant guidance about appropriate approaches that take into account the local needs and the specific cultural, legal, and ecological context in which such instruments are being developed and applied. This paper presents a step-by-step framework that helps conservation and development plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 51 publications
1
32
0
2
Order By: Relevance
“…For example, many education programs and social marketing campaigns may seek to change people's mental models or alter intrinsic motivations through creating connections with nature and changing people's ethics, values or beliefs (McKenzie-Mohr et al 2011;Leisher et al 2012). Payments for environmental service (PES) programs were originally designed to provide external financial rewards for engaging in stewardship (Wunder 2007), thus targeting extrinsic motivations, though PES programs are becoming more nuanced in how they are designed to match a variety of local motivations (Rode et al 2016). Some stewardship programs focus on building stewardship networks, at times introducing new actors or organizations to facilitate these processes (Kowalski and Jenkins 2015;Jenkins et al 2017).…”
Section: Stewardship Interventionsmentioning
confidence: 99%
“…For example, many education programs and social marketing campaigns may seek to change people's mental models or alter intrinsic motivations through creating connections with nature and changing people's ethics, values or beliefs (McKenzie-Mohr et al 2011;Leisher et al 2012). Payments for environmental service (PES) programs were originally designed to provide external financial rewards for engaging in stewardship (Wunder 2007), thus targeting extrinsic motivations, though PES programs are becoming more nuanced in how they are designed to match a variety of local motivations (Rode et al 2016). Some stewardship programs focus on building stewardship networks, at times introducing new actors or organizations to facilitate these processes (Kowalski and Jenkins 2015;Jenkins et al 2017).…”
Section: Stewardship Interventionsmentioning
confidence: 99%
“…The legal dimension in the framework of Karsenty and colleagues may partially explain the observation by Wong and colleagues in Vietnam of the inadequate incentive effect relative to economic costs incurred. Of course, there may be a number of other motivational explanations that explain PES impacts (Rode et al, 2016). The 'PES hybridization' framework of Karsenty and colleagues also complements the Pannell (2008) public-private benefit framework for targeting policy instruments.…”
Section: Complementary Policy MIX Analysis Frameworkmentioning
confidence: 99%
“…Thus, for successful and efficient environmental management, both the ecosystems and societies need to be considered. As a result, the challenge for policymakers has also expanded to understanding human preferences for the environment (Rode et al, 2016;Pascual et al, 2017). In fact, as Oldekop et al (2015) suggested, conservation targets are more likely to be achieved when socioeconomic benefits are encouraged through sustainability rather than when they are imposed through strict protection.…”
Section: Introductionmentioning
confidence: 99%